2019
DOI: 10.1055/s-0039-1690707
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II)-Catalyzed C–N Coupling of Aryl Halides and N-Nucleophiles Promoted by Quebrachitol or Diethylene Glycol

Abstract: Herein, we report the natural ligand quebrachitol (QCT) as a promoter for a Cu(II) catalyst, which is highly effective for N-arylation of various amines and related aryl halides. A series of diarylamine derivatives were obtained in high yields by using diethylene glycol (DEG) as both ligand and solvent. The C–N coupling reactions proceed under mild conditions and exhibit good functional group tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…no., 504-29-0; structure, Figure ) is widely employed in a variety of applications of pharmaceuticals’ synthesis, especially for antihistamines, antiflammatories, and other drugs. , Brominated 2-aminopyridine attracted considerable attention for its applications as useful intermediates or building blocks for pharmaceuticals. In particular, 2-aminopyridine also serves as an useful raw material for some liquid crystals. , Regardless of its wide applications, there has been little research into the thermodynamic properties of 2-aminopyridine in neat and mixed solvents. 2-Aminopyridine is generally obtained through the reduction of 2-nitropyridine or 2-halopyridine in various solvents such as ethanol, , methanol, acetonitrile, N -methyl-2-pyrrolidine (NMP), and so on. Therefore the solubility of 2-aminopyridine in various solvents has a significant impact on product yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…no., 504-29-0; structure, Figure ) is widely employed in a variety of applications of pharmaceuticals’ synthesis, especially for antihistamines, antiflammatories, and other drugs. , Brominated 2-aminopyridine attracted considerable attention for its applications as useful intermediates or building blocks for pharmaceuticals. In particular, 2-aminopyridine also serves as an useful raw material for some liquid crystals. , Regardless of its wide applications, there has been little research into the thermodynamic properties of 2-aminopyridine in neat and mixed solvents. 2-Aminopyridine is generally obtained through the reduction of 2-nitropyridine or 2-halopyridine in various solvents such as ethanol, , methanol, acetonitrile, N -methyl-2-pyrrolidine (NMP), and so on. Therefore the solubility of 2-aminopyridine in various solvents has a significant impact on product yield.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Regardless of its wide applications, there has been little research into the thermodynamic properties of 2-aminopyridine in neat and mixed solvents. 2-Aminopyridine is generally obtained through the reduction of 2-nitropyridine or 2-halopyridine in various solvents such as ethanol, 12,13 methanol, 14 acetonitrile, 15 Nmethyl-2-pyrrolidine (NMP), 16 and so on. Therefore the solubility of 2-aminopyridine in various solvents has a significant impact on product yield.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As far as the gold-catalyzed 1,2-aminoarylation of alkenes is concerned only intramolecular versions are known, and to date there are no reports where external amines are used as coupling partners. This could be mainly attributed to the fact that amines, especially anilines, are highly prone to undergo direct coupling with aryl iodides under Pd, Cu, or Ni catalysis . Even, our group and soon after Bourissou’s group reported that such C–N cross-coupling reactions are feasible under gold catalysis utilizing MeDalPhosAuCl as a catalyst. , Bypassing this highly facile C–N cross-coupling reaction would be a major hurdle in this type of scenario.…”
mentioning
confidence: 96%